Crisis of Spirituality in The Waste Land of T. S. Eliot - Sharma, Til Kumari (A Bi-annual South Asian Journal of Research & Innovation, 2023)
The article has tried to depict the spiritual loss in 20th century through the poem The Waste Land. Eliot seems very popular feature of the modern time. He was born in 1888 in America and died in 1965 in England. He is recognized as an American-English author of 20th century. His life had been nourished with many ups and downs of war time. He also had got complexities and tension in his life time. He left his nation for his survival. He has shown the crisis of modern time with his poem in which spiritual value is empty in everybody. Eliot’s life comes with lone struggle. His verse has mirrored the culture as it is. It has depicted fashion, death, destruction, passion, sex-oriented love and kind less human heart. The inhumanity was big amount in modern time. No true heart was found there. The fashionable world with poor society had lost the dignity. The true love was nowhere. So the spiritual crisis seemed to appear everywhere. Modern period was ill by battlefield and lust. The people of society were not with kind heart and calmness. The time was born only with materialistic thought. As a result, the spirituality was in mist. This verse was composed by Eliot to show the crisis of spiritual world. So, crisis of inhumanity seemed in war time everywhere. The society seemed motionless. The life was in materialistic modern period.